HYDROGEOCHEMICAL VARIABILITY BETWEEN WET AND DRY SEASONS IN LAGOS STATE, NIGERIA - Nwosu , Emmanuel Chukwudi; Amadi , Precious Chisom; Ogbonda , Ifeanyi Godwin (Ayden Journal of Engineering and Applied Sciences, 2025)
This study evaluates hydrogeochemical variations across five land-use zones in Lagos, Nigeria, A total of 25 groundwater samples were analyzed for physicochemical parameters and seven heavy metals—arsenic, cadmium, chromium, copper, nickel, lead, and mercury—using methodologies such as inductively coupled plasma-optical emission spectrometry (ICP-OES). A total of 25 groundwater samples in 25 locations and 5 land uses using strict sample collection procedure. Samples were taken to the laboratory, prepared and analysed for trace metals content using inductively coupled plasma mass spectrometry (ICP-MS). All physicochemical parameters were analysed in-situ. Statistical analysis was done using Microsoft office excel, SPSS and R-Studio. The result of Physico-chemical parameters in this study were pH 5.13±0.46 to 7.10±0.16, EC 114.28±14.11 to 303.62±92.67µS/cm, Salinity 0.01±0.00 to 0.10±0.04ppt, TDS 42.25±4.55mg/l to 131.05±40.29mg/l and Temperature 26.06±0.310C to 26.28±0.110C. the results of the metals include; Ag 0.00±0.00mg/l to 0.06±0.02mg/l; Al 0.06±0.02 to 0.25±0.10mg/l; As 0.00±0.00 to 0.04±0.00m/l, B 0.03±0.00 - 1.93±1.26mg/l; Ca 2.07±0.23 to 14.54±7.73mg/l, Co 0.01±0.00 to 0.07±0.00mg/l, Cr 0.00±0.00 to 0.06±0.01mg/l, Cu 0.02±0.01 to 0.17±0.05mg/l; Hg 0.00±0.00, K 0.97±0.04 to 21.10±7.73mg/l; Li 0.00±0.00 to 0.02±0.00mg/l; Mg 0.18±0.03 to 4.13±1.58mg/l; Mn 0.01±0.00 to 0.44±0.14mg/l; Na 9.27±0.38 to 22.08±4.89mg/l; Ni 0.00±0.00 to 0.03±0.02mg/l; Fe 0.03±0.00 to 0.92±0.11mg/l; Cd 0.00±0.00 to 0.01±0.01; Zn 0.03±0.00 to 1.69±0.83 and Pb 0.00±0.00 to 0.22±0.21mg/l. The Elevated levels of Lead, Arsenic and Nickel from the groundwater especially from the Dumpsites and Agricultural lands are resultant from the associated impact of waste deposits and agricultural activities within the study area. The estimated daily intake (EDI) of metals in both wet and dry seasons were below the Reference dose (RfD) except for calcium. The hazard quotients (HQ) of metals across the land uses exhibited low non-cancer health risk. There is no carcinogenic risk directed to the exposed populace as a result of ingestion of the metals via water consumption. These findings underscore the need for adaptive groundwater management strategies in Lagos State